Stress assessment by neuro-humoral evaluation in elite pentathletes - Pigozzi, F. M; Iellamo, F.; Parisi, A.; Vago, T.; Norbiato, G.; Lucini, D.; Pagani, M. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
In elite athletes integrated stress assessment may be of paramount importance for individual titration of optimal training or early recognition of incipient "overtraining". In these conditions the neurovegetative and neuro-humoral systems play a crucial role. However, to date a reliable tool for assessing stress induced changes in autonomic and neuro-hormonal control in athletes is lacking.